ANALISIS PENGARUH GAYA KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP KINERJA BAWAHAN (STUDI EMPIRIS PADA PERGURUAN TINGGI SWASTA DI KOTA SEMARANG) - Untung Widodo (STIE Pelita Nusantara Semarang, 2006)
The work way from the lower workers are in fluenced by the upper's leaderhip. The leadership style has impacted which is significant to the attitude of the lower workers. The effectiveness of a leader will be very influenced by the lower characteristic. Where as the work satisfaction on the work way shows the low relation between the work satisfaction and the work way, that will showthe level organisation, the work satisfaction that influenced the productivity and profitability with the lower workers who has less satisfaction.